2015
DOI: 10.1111/ijpo.12073
|View full text |Cite
|
Sign up to set email alerts
|

Age at spermarche: 15‐year trend and its association with body mass index in Chinese school‐aged boys

Abstract: . (2016). Age at spermarche: 15-year trend and its association with body mass index in Chinese school-aged boys. Pediatric obesity, 11(5), 369-374. DOI: 10.1111/ijpo.12073 General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 27 publications
(75 reference statements)
2
29
0
Order By: Relevance
“…Among those who had experienced menarche or spermarche (97.3% of girls and 74.5% of boys), the mean grade of menarche or spermarche was 8.13 ± 1.8 for boys and 7.27 ± 1.3 for girls. The average grade by which menarche/spermarche were achieved were similar to those reported previously (Negriff & Susman, 2011;Song et al, 2015).…”
Section: Covariatessupporting
confidence: 87%
“…Among those who had experienced menarche or spermarche (97.3% of girls and 74.5% of boys), the mean grade of menarche or spermarche was 8.13 ± 1.8 for boys and 7.27 ± 1.3 for girls. The average grade by which menarche/spermarche were achieved were similar to those reported previously (Negriff & Susman, 2011;Song et al, 2015).…”
Section: Covariatessupporting
confidence: 87%
“…One explanation is that Chinese girls prefer to be slim leading to dietary restriction (23.6% in girls vs. 9.1% in boys according to a national survey in 2005) and thus benefit less from food availability or diversity (Song, Wang, Ma, & Wang, ). Alternatively, school‐aged girls enter puberty about 2 years earlier (Song et al, ; Song et al, ), and menstruation may increase girls' vulnerability to anaemia (Friedman et al, ) and lesser reduction with economic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, school-aged girls enter puberty about 2 years earlier (Song et al, 2014;Song et al, 2016), and menstruation may increase girls' vulnerability to anaemia (Friedman et al, 2012) and lesser reduction with economic growth.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have examined the relationship between puberty and body mass index (BMI) among boys by using different measures [e.g., voice break, age at onset of pubertal growth spurt, peak height velocity, public hair growth, testicular volume, and/or penis length], and the results reported have been inconsistent 17, 18, 19, 20, 21. However, a recent study examining the trend of age at spermarche and its association with BMI among Chinese school boys found that a higher BMI or BMI-for-Age z -score was associated with an increased likelihood of having reached spermarche, indicating the overlapping trend of earlier age at spermarche with increase in BMI over the past 15 years among Chinese boys [3].…”
Section: Introductionmentioning
confidence: 99%